Sex-dependent long-term effects of prepubescent stress on the posterior parietal cortex - Fariborzi, Mona (Neurobiol Stress, 2021)
Adolescence is a time of intense cortical development and a period of heightened sensitivity to insult. To determine how sex affects the short- and long-term outcomes of early-adolescent stress exposure, we subjected prepubescent (postnatal day 30) male and female mice to repeated multiple concurrent stressors (RMS). In the posterior parietal cortex (PPC), RMS caused the elimination of excitatory synapses in deeper layers while inhibitory synapse density was predominantly diminished in superficial layers. These short-term effects coincided with reduced visuo-spatial working memory and were similar in both sexes. The loss of excitatory synapses and impaired working memory persisted in males past a 30-day recovery period. In contrast, we observed a remarkable recovery of excitatory transmission and behavioral performance in females. Inhibitory synapse density recovered in both sexes. We have also observed a late onset anxiety phenotype in RMS exposed females that was absent in males. Overall, our results indicate that there are marked sex differences in the long-term effects of prepubescent stress on cortical synapses and behavior.